Case report: Brief, intensive EMDR therapy for borderline personality disorder: results of two case studies with one year follow-up - Hafkemeijer, Laurian; Slotema, Karin; Haard, Nicole de; Jongh, Ad de (Frontiers in Psychiatry, 2023)
Exposure to adverse childhood events plays an important role in the development of borderline personality disorder (BPD). Emerging evidence suggests that trauma-focused therapy using eye movement desensitization and reprocessing (EMDR) can be beneficial for patients with BPD symptoms. To date, the effects of brief, intensive EMDR treatment for this target group have not been investigated in this population.This study aimed to evaluate the effects of a brief and intensive trauma-focused therapy course using EMDR therapy in two patients diagnosed with BPD who did not fulfill the diagnostic criteria for post-traumatic stress disorder (PTSD). It was hypothesized that this approach would be associated with a decline in the core symptoms of BPD, and that this would have an enduring long-term effect on patients' diagnostic status.Ten sessions of EMDR therapy were carried out across four consecutive treatment days, with the aim of processing patients' core adverse childhood experiences. Both A-criterion-worthy memories (without intrusive reliving) and non-A-criterion-worthy memories that were considered responsible for the patients' most prominent symptoms were targeted. The effects of EMDR therapy on trauma symptom severity and BPD diagnostic status (as established by the Structured Clinical Interview DSM-5) were determined. Additionaly, the effects on psychological distress, quality of life, and difficulties in emotion regulation were determined at intake, post-treatment, and at 3-, 6-and 12-months follow-up.Both patients showed a strong decline in psychological distress and difficulties in emotion regulation, and reported an improvement in their quality of life. At post-treatment, and at 3-, 6and 12-months follow-up they no longer met the DSM-5 criteria for BPD.The findings of this small case study are in line with mounting evidence that a brief track of intensive trauma-focused therapy can result in long-term remission in patients with BPD. EMDR therapy seems to be a promising treatment approach for patients with BPD; however, the results need to be replicated in clinical trials.